Connecting Cities with Macro-economic Concerns : The Missing Link - Freire, Mila (The World Bank, 2003)
This book examines the influence of local public services on the economics of cities. The relationship between economic development and urbanization is indisputable; less clear, however, are the ways in which cities directly contribute to economic growth and employment creation. Current economic thinking holds that the ability of cities to create wealth depends on "agglomeration economies;" that is, the geographic concentration of industries and people which enables economic actors to come together, interact, and become productive. However, this ability to promote productive interaction depends on several factors, one of which is the provision of local public services. The book argues that the quality of local services significantly influences the productivity of a city, and of its business firms. Inferior local services increase the cost of interaction, erode the effects of agglomeration, and diminish wealth-creation potential. This study attempts to assess the costs of inferior local public services to firms. Based on surveys conducted in five cities-Belo Horizonte (Brazil), Montreal (Canada), Puebla (Mexico), San José (Costa Rica), and San Salvador (El Salvador)-it examines the complex issues surrounding local service provision, and illustrates how inferior local services affect firms and, in turn, the ability of firms to contribute to wealth